Pengembangan Media Pembelajaran Interaktif Berbasis Komputer Untuk Siswa SMP Kelas VIII - Arda Arda; Sahrul Saehana; Darsikin Darsikin (Mitra Sains, 2015)
This research aimed to result computer-based interactive learning media for eighth grade students of Junior High School. Developed interactive learning media consisted of two main parts: material and evaluation. The procedure of development followed Borg and Gall model. The interactive learning was validated by material and media experts. The material validation result was in very good category and media validation was in good category. The media was tried out at SMP Negeri 3 Palu. The students’ response in small and large-scale try out were in very good category. The students’ learning achievement showed an improvement where normalized gain (<g>) was in moderate category. The results showed that developed interactive learning media is feasible to use as an learning media in supporting conceptual understanding.